2001
DOI: 10.1134/1.1378871
|View full text |Cite
|
Sign up to set email alerts
|

Quark combinatorics and meson-production ratios in hadronic Z 0 decays

Abstract: Rich experimental data accumulated in the past few years in the hadronic Z 0 decays allow one to check the quark combinatorics relations for a new type of processes, namely: quark jets in the decays Z 0 → qq → hadrons. In this paper we review quark combinatorics rules for the yields of vector and pseudoscalar mesons, V /P , in the central and fragmentation regions of the hadronic Z 0 decays. It is stressed that in the central region a direct verification of quark combinatorics rules is rather problematic becau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For usually accepted value λ ≈ 0.3, this prediction is a factor of more than two higher than the experimental values at large x p . It deviates from the DELPHI value of 0.14 ± 0.02 at x p = 0.85 by 7 standard deviations or even more for λ ≈ 0.5 suggested in [5].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…For usually accepted value λ ≈ 0.3, this prediction is a factor of more than two higher than the experimental values at large x p . It deviates from the DELPHI value of 0.14 ± 0.02 at x p = 0.85 by 7 standard deviations or even more for λ ≈ 0.5 suggested in [5].…”
mentioning
confidence: 99%
“…Recently Anisovich et al [5] compared these predictions with the LEP data. They analyzed the V /P ratios obtained from the ALEPH data [6] at large x p = p/p beam → 1, where a contribution of the resonance decays is supposed to be strongly suppressed, and concluded that the experimental results are consistent with V /P = 3.…”
mentioning
confidence: 99%
See 3 more Smart Citations